Relationship between body composition, sprint performance and vertical jump tests in young elite soccer players - Gameiro, Pedro (2019)
Poster presented at the 2nd International Congress of CiiEM - Translational Research and Innovation in Human and Health Science. 11-13 June 2017, Campus Egas Moniz, Caparica, Portugal